2015
DOI: 10.1371/journal.pone.0129788
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Protects against Cadmium-Induced Hepatotoxicity in Rats via GJIC and MAPK Pathways

Abstract: It is known that cadmium (Cd) induces cytotoxicity in hepatocytes; however, the underlying mechanism is unclear. Here, we studied the molecular mechanisms of Cd-induced hepatotoxicity in rat liver cells (BRL 3A) and in vivo. We observed that Cd treatment was associated with a time- and concentration-dependent decrease in the cell index (CI) of BRL 3A cells and cellular organelle ultrastructure injury in the rat liver. Meanwhile, Cd treatment resulted in the inhibition of gap junction intercellular communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…We first sought to determine whether cadmium can induce morphological changes and cell death in H9‐CMs. Previous studies have investigated cadmium‐induced cytotoxicity in different cell types within a range of 0‐300 μmol/L . Therefore, cells were exposed to escalating concentrations of cadmium chloride (CdCl 2 ) from 0.1 to 100 μmol/L for 24 hours, and significantly morphological changes appeared in cells treated with 30 and 100 μmol/L CdCl 2 (Videos ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first sought to determine whether cadmium can induce morphological changes and cell death in H9‐CMs. Previous studies have investigated cadmium‐induced cytotoxicity in different cell types within a range of 0‐300 μmol/L . Therefore, cells were exposed to escalating concentrations of cadmium chloride (CdCl 2 ) from 0.1 to 100 μmol/L for 24 hours, and significantly morphological changes appeared in cells treated with 30 and 100 μmol/L CdCl 2 (Videos ).…”
Section: Resultsmentioning
confidence: 99%
“…To relate changes in gene expression to functional consequences, we next investigated MAPK signalling pathway, which was associated with cadmium‐induced apoptosis of several cell types in previous studies and was dramatically up‐regulated in CdCl 2 ‐treated H9‐CMs …”
Section: Resultsmentioning
confidence: 99%
“…What is more, Sal protects myocardia from IRI in rats by inhibiting apoptosis and inflammation 24. In addition, Sal inhibits MAPK signal transduction to protect organs from damaging factors, such as cardiac exhaustive injury, cadmium-induced hepatotoxicity, and cigarette smoke-induced lung diseases 18,25. Therefore, it is reasonable to infer that Sal could protect hepatic IRI through the downregulation of MAPKs to inhibit inflammation, apoptosis, and autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe and Asia, R. crenulata is a traditional drug with efficacy in stimulating the nervous system, reducing depression, enhancing work capacity, promoting fatigue recovery, and preventing altitude sickness (Ishaque, Shamseer, Bukutu, & Vohra, 2012;Kelly, 2001;Lee, 1998). Unofficially, R. crenulata has been used as a fever reducer, sedative, and astringent and has been reported to show antioxidant, anti-inflammatory, antidiabetic, and liver toxicity protection activities (Choe et al, 2012;Kwon, Jang, & Shetty, 2006;Wu, Lian, Jiang, & Nan, 2009;Zou et al, 2015). Recently, researchers have reported that R. crenulata has additional beneficial effects, including antioxidant activity (Kanupriya et al, 2005) and protection against neuron damage (Mook-Jung et al, 2002).…”
Section: Introductionmentioning
confidence: 99%